A Cultural History of Youth in the Modern Age - Sleight, Simon; Alexander, Kristine (The Cultural Histories Series, 2022)
This open access volume of A Cultural History of Youth, The Modern Age, explores the cultural history of youth from 1920 to the present day. With each chapter dedicated to a specific theme, it covers concepts of youth; spaces and places; education and work; leisure and play; emotions, gender, sexuality and the body; belief and ideology; authority and agency; war and conflict and towards a world history. Readers can trace one theme throughout history using all six volumes, or can gain an in-depth understanding of an individual period. A Cultural History of Youth presents historians, scholars and students of related fields with a comprehensive and interdisciplinary overview of youth from ancient times to modernity. With six highly illustrated volumes covering 2,500 years, they each focus on a specific period; Antiquity, the Medieval Age, the Renaissance, the Enlightenment, the Age of Empire and the Modern Age. The open access edition of this book is available under a CC-BY-ND 3.0 license on bloomsburycollections.com. Open access was funded by The Social Sciences and Humanities Research Council of Canada.